DEVELOPMENT OF UNIVERSITY LIBRARY IN THE MEDIA SPACE - Turanskaya, Yevheniia D. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
We consider the mass media aspect of the university library activity. Examples of individual virtual projects are presented.